Soft Photonic Fibers for Colorimetric Solvent Vapor Sensing. Issue 13 (4th May 2020) - Malekovic, Mirela; Urann, Markus; Steiner, Ullrich; Wilts, Bodo D.; Kolle, Mathias
Abstract: Stimuli‐responsive elastomers are promising material systems for the development of optical sensors with visual outputs that can be easily assessed by the human eye. These materials, when shaped into alternating layers, form distributed Bragg reflectors (DBRs) that feature a high spectrally selective reflectivity. The adsorption of vapor molecules into these photonic structures leads to partial swelling in the constituent materials that can induce pronounced color changes. Here, it is demonstrated that soft photonic fibers with a DBR‐cladding can selectively sense and quantify different organic vapors. It is found that fibers with a multilayer cladding assembled of films of polydimethylsiloxane (PDMS) and a polystyrene‐polyisoprene block‐copolymer (PSPI) change color sensitively depending on the concentration of toluene, benzene, tetrahydrofuran, or chloroform vapors. It is shown that this is a direct consequence of a selective swelling of the constituent polymer layers due to vapor adsorption. With wavelength variations as small as 5 nm being noticeable to the human eye, such photonic fibers are interesting materials for optical sensors. Modifications of their building blocks and their structural morphology make these vapor‐sensing fibers a versatile platform for standalone and textile‐integrated solvent sensing systems applied in industrial and lab‐scale manufacturing processes. Abstract : Soft, multilayered photonic fibers are used as gas sensors to quantify different process gases via perceivable color variations. The photonic fiber design combines the gas‐specific elastic response of different polymers with a controlled structuring method. This proof‐of‐concept approach should readily allow the development of gas‐specific color sensors.